The native microbiome of the nematode Caenorhabditis elegans: gateway to a new host-microbiome model. Issue 1 (December 2016) - Dirksen, Philipp; Marsh, Sarah; Braker, Ines; Heitland, Nele; Wagner, Sophia; Nakad, Rania; Mader, Sebastian; Petersen, Carola; Kowallik, Vienna; Rosenstiel, Philip; Félix, Marie-Anne; Schulenburg, Hinrich
Abstract Background Host-microbe associations underlie many key processes of host development, immunity, and life history. Yet, none of the current research on the central model speciesCaenorhabditis elegans considers the worm's natural microbiome. Instead, almost all laboratories exclusively use the canonical strain N2 and derived mutants, maintained through routine bleach sterilization in monoxenic cultures with anE. coli strain as food. Here, we characterize for the first time the native microbiome ofC. elegans and assess its influence on nematode life history characteristics. Results Nematodes sampled directly from their native habitats carry a species-rich bacterial community, dominated by Proteobacteria such as Enterobacteriaceae and members of the generaPseudomonas, Stenotrophomonas, Ochrobactrum, andSphingomonas . TheC. elegans microbiome is distinct from that of the worm's natural environment and the congeneric speciesC. remanei . Exposure to a derived experimental microbiome revealed that bacterial composition is influenced by host developmental stage and genotype. These experiments also showed that the microbes enhance host fitness under standard and also stressful conditions (e.g., high temperature and either low or high osmolarity). Taking advantage of the nematode's transparency, we further demonstrate that several Proteobacteria are able to enter theC. elegans gut and that anOchrobactrum isolate even seems to be able to persist in the intestines under stressful conditions. Moreover, threePseudomonas isolates produce an anti-fungal effect in vitro which we show can contribute to the worm's defense against fungal pathogens in vivo. Conclusion This first systematic analysis of the nematode's native microbiome reveals a species-rich bacterial community to be associated withC. elegans, which is likely of central importance for our understanding of the worm's biology. The information acquired and the microbial isolates now available for experimental work establishesC. elegans as a tractable model for the in-depth dissection of host-microbiome interactions.